2018
DOI: 10.1038/s41598-018-33353-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspirin-loaded graphene oxide coating of a titanium surface on proliferation and osteogenic differentiation of MC3T3-E1 cells

Abstract: Graphene oxide (GO) has attracted considerable attention for biomedical applications such as drug delivery because of its two-dimensional structure, which provides a large surface area on both sides of the nanosheet. Here, a new method for titanium (Ti) surface modification involving a GO coating and aspirin (A) loading (A/Ti-GO) was developed, and the bioactive effects on mouse osteoblastic MC3T3-E1 cells were preliminarily studied. The X-ray photoelectron spectrometry indicated new C-O-N, C-Si-O-C, and C-N=C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Additionally the anti-inflammatory effect was concomitant with a down-regulation of IL-10, IL-6 and TNF-α [19]. Other researchers also found that icariin possess significant therapeutic effect on rheumatoid arthritis (RA) clinically [9]. Moreover, the mechanism of icariin to prevent RA might be related to its immunoregulatory function, which was mediated through the decrease in the cell number of immune cells Th17.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally the anti-inflammatory effect was concomitant with a down-regulation of IL-10, IL-6 and TNF-α [19]. Other researchers also found that icariin possess significant therapeutic effect on rheumatoid arthritis (RA) clinically [9]. Moreover, the mechanism of icariin to prevent RA might be related to its immunoregulatory function, which was mediated through the decrease in the cell number of immune cells Th17.…”
Section: Discussionmentioning
confidence: 98%
“…Among them, the application of protein growth factor on implant surface has been proved to be an effective way for enhancing osteogenesis and could accelerate osseointegration at the implant-tissue interface, such as bone morphogenetic protein-2 [6][7][8]. However, the lack of chemical stability of growth factor proteins hinders their wide application in implant surface modification [8,9]. In addition, inflammation reaction generated during the drilling, screwing and inserting processes of implant surgery may hamper bonding strength between implant and surrounding bone tissue [10].…”
Section: Introductionmentioning
confidence: 99%
“…A live-dead assay can help to evaluate cell cytotoxicity of the scaffolds as well as clarify cell status, a potential confounding factor for myogenic differentiation. However, WST-8 assay is a commonly used tool for cytotoxicity testing since it is sensitive and reproducible [ 34 ]. The amount of formazan dye generated is directly proportional to the number of living cells and several groups have used this assay for evaluating new biomaterials or tissue engineered constructs [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, WST-8 assay is a commonly used tool for cytotoxicity testing since it is sensitive and reproducible [ 34 ]. The amount of formazan dye generated is directly proportional to the number of living cells and several groups have used this assay for evaluating new biomaterials or tissue engineered constructs [ 34 36 ]. WST-8-assay showed higher viability for ADSC compared to BMSC, indicating higher proliferation capacity, which has also been shown by others [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although experts and scholars have performed many in vitro cytological studies investigating the surface modification of implants, to date, they have not designed, developed and verified an oral implant with good osseointegration in an in vivo model, and the domestic implants independently developed in China have not been recognized by most dental implant doctors and patients 26 , 27 . Therefore, in the current study, a new type of implant was developed and verified in vivo with beagle dogs, and the differences in the osseointegration properties between the novel implant and a commercial implant (Straumann SLActive) were observed and compared by using micro-CT and histology methods to identify the scientific basis of the osseointegration of the new implant.…”
Section: Introductionmentioning
confidence: 99%